PERAN MEDIA SOSIAL DALAM MEMBANGUN BRAND IMAGE PRODUK WARDAH - Suryasuciramdhan, Arfian; Zulfikar, Meiby; Gusliani, Ani; Sulistiawati, Sulistiawati; Jumiah, Jumiah (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Your research objective, which explores the influence of social media marketing and influencer marketing on consumer purchasing decisions, is very relevant in the context of modern marketing. By understanding how these two factors influence consumer behavior, companies can design more effective marketing strategies to increase sales of their products. In this research, you can explore various aspects, including the types of content that are most effective in influencing purchasing decisions, the role of influencers in shaping consumer preferences, and the impact of social media interactions on consumer attitudes towards brands or products. Thus, the results of this research can provide valuable insight for companies in designing more effective and targeted marketing strategies, as well as understanding consumer behavior in the ever-growing digital era. This research uses a quantitative research approach, which involves collecting and analyzing quantitative data to test hypotheses and produce broader generalizations. Data was collected through questionnaires or statement sheets given to respondents, who in this case were consumers of Wardah Cosmetics products in Serang City. The analytical method used is multiple linear regression analysis, which allows researchers to test the relationship between several independent variables (in this case, social media variables) and one dependent variable (Wardah brand image) simultaneously. The research results show that social media has a significant influence on the brand image of Wardah products. This shows that social media activities, such as promotions, interactions with consumers, and shared content, have a positive impact on consumer perceptions of the Wardah brand as a whole. This conclusion provides important insight for companies in understanding the importance of social media in building and strengthening the brand image of their products. This emphasizes the importance of effective marketing on social media platforms to influence consumer perceptions and increase brand loyalty